The effectiveness of the interventions of the Swiss National Bank: an event-study analysis - Christian Pierdzioch; Georg Stadtmann (Kiel Institute for World Economics (IfW), 2003)
We use the event-study methodology to analyze the effectiveness of the foreign exchange market interventions conducted by the Swiss National Bank (SNB) during the period from 1986 through 1995. We find some evidence that the interventions of the SNB had an impact on exchange rate dynamics. The significance of this effect, however, depends on the direction of intervention. In general, the evidence suggests that the interventions of the SNB to strengthen the Swiss franc were more effective than its interventions to weaken the Swiss franc. We also find that the results of the tests for the effectiveness of the interventions of the SNB depend upon the length of the pre- and post-event window analyzed.
Keywords: F31; F33; G14; 330; Foreign exchange market; Central bank intervention; Swiss National Bank; Wechselkurspolitik; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Schweiz; Event study